The chicken model of spontaneous ovarian cancer. Issue 9 (October 2014) - Hawkridge, Adam M.
Abstract : The chicken is a unique experimental model for studying the spontaneous onset and progression of ovarian cancer (OVC). The prevalence of OVC in chickens can range from 5 to 35% depending on age, genetic strain, reproductive history, and diet. Furthermore, the chicken presents epidemiological, morphological, and molecular traits that are similar to human OVC making it a relevant experimental model for translation research. Similarities to humans include associated increased risk of OVC with the number of ovulations, common histopathological subtypes including high‐grade serous, and molecular‐level markers or pathways such as CA‐125 expression and p53 mutation frequency. Collectively, the similarities between chicken and human OVC combined with a tightly controlled genetic background and predictable onset window provides an outstanding experimental model for studying the early events and progression of spontaneous OVC tumors under controlled environmental conditions. This review will cover the existing literature on OVC in the chicken and highlight potential opportunities for further exploitation (e.g. biomarkers, prevention, treatment, and genomics).